Modelling track cycling standing start performance: combining energy supply and energy demand - Flyger, N.; Froncioni, A.; Martin, D. T.; Billaut, F.; Aughey, R. J.; Martin, J. C. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
To date there has been limited practical application of energy supply models to sprint cycling performance due to difficulties in determining complex physiological parameters or oversimplifications limiting relevance to steady state performance. Here an energy supply and demand model is presented for track cycling drawing on research incorporating forward integration energy demand modelling, the Power-Cadence relationship in maximal sprint cycling, rate of fatigue per revolution relative to maximum power and the critical power model. All input parameters can be determined from simple field or laboratory testing and even training data. The model successfully predicted an elite cyclist`s timed 250-m performance from stationary start to within 0.31%.